Does CYP2E1 RsaI/PstI polymorphism confer head and neck carcinoma susceptibility?: A meta-analysis based on 43 studies. Issue 43 (October 2016) - Zhuo, Xianlu; Song, Jue; Liao, Jian; Zhou, Wei; Ye, Huiping; Li, Qi; Xiang, Zhaolan; Zhang, Xueyuan
Abstract: Background: Previous reports showed that CYP2E1 RsaI/PstI polymorphism may be a risk factor for cancers. Published meta-analyses in 2010 and 2011, respectively, on the relationship of CYP2E1 RsaI/PstI polymorphisms with the susceptibility to head and neck carcinoma (HNC) have generated inconsistent results. Thus, this study aimed to conduct an updated meta-analysis involving published studies up to Nov 2015 to get a more confidential result. Methods: Eligible studies up to Nov 2015 were retrieved and screened. Data were extracted and a quantitative meta-analysis was conducted. Subgroup analyses on ethnicity, source of controls, sample size, genotyping method, smoking status, and drinking status were also performed. Results: Forty-one publications including a total of 43 case-control studies were selected for analysis. The overall data under a homozygote comparison model indicated a significant association of CYP2E1 RsaI/PstI polymorphisms with HNC risk (c2c2 vs c1c1: odds ratio [OR] = 1.97; 95% confidence interval [CI] = 1.53–2.53). Similar results were observed in the Asian subgroup (c2c2 vs c1c1: OR = 1.98; 95%CI = 1.51–2.60; c2 vs c1: OR = 1.20; 95%CI = 1.03–1.39) and mixed population (c2 vs c1: OR = 1.41; 95%CI = 1.06–1.86) when the data were stratified by ethnicities. Interestingly, increased cancer risk only was shown among never-smokers (c2c2+c1c2 vs c1c1: OR = 1.44; 95%CI = 1.05–1.98) but not ever-smokers. Conclusion: CYP2E1 RsaI/PstI polymorphisms may modify the susceptibility to HNC, particularly among Asians, mixed population, and never-smokers. Future large and well-designed studies are needed to verify this conclusion.